1999
DOI: 10.1002/(sici)1521-4184(199910)332:10<363::aid-ardp363>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Calcium Channel Antagonist Activity, and Anticonvulsant Activity of 3-Ethyl 5-Methyl 1,4-Dihydro-2-[(2-hydroxyethoxy)methyl]-6-methyl-4-(2,3-dichlorophenyl)-3,5-pyridinedicarboxylate Coupled to a 1-Methyl-1,4-dihydropyridyl-3-carbonyl Chemical Delivery System

Abstract: 3‐Ethyl 5‐methyl 1,4‐dihydro‐2‐[(2‐hydroxyethoxy)methyl]‐6‐methyl‐4‐(2,3‐dichlorophenyl)‐3,5‐pyridinedicarboxylate (13), a bioisostere of amlodipine, was prepared by the reaction of ethyl 4‐(2‐hydroxyethoxy)acetoacetate (11) with methyl 2‐(2,3‐dichlorobenzylidene) acetoacetate (12) and NH4OAc. Compound 13 was elaborated to the target product 3‐ethyl 5‐methyl 1,4‐dihydro‐2‐[2‐[(1‐methyl‐1,4‐dihydropyridyl‐3‐carbonyloxy)ethoxy]methyl]‐6‐methyl‐4‐(2,3‐dichlorophenyl)‐3,5‐pyridinedicarboxylate (16). The C‐2 CH2OCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The main antihypertensive action, however, is still without question via blockade of the L-type calcium channels, where their potency is normally in the 1 to 10 nmol/L range. 13,14 In contrast, the lowest MR IC50 is still above 100 nmol/L. Only when high doses are used or if compound accumulates in particular tissues can there be substantial effect on MR.…”
Section: Discussionsupporting
confidence: 66%
“…The main antihypertensive action, however, is still without question via blockade of the L-type calcium channels, where their potency is normally in the 1 to 10 nmol/L range. 13,14 In contrast, the lowest MR IC50 is still above 100 nmol/L. Only when high doses are used or if compound accumulates in particular tissues can there be substantial effect on MR.…”
Section: Discussionsupporting
confidence: 66%
“…In addition it has been shown that lipophilic 4-(2,3-dichlorophenyl) or 4-imidazolyl-1,4-dihydropyridines have anticonvulsant activity (Yiu and Knaus, 1999;Navidpour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Knuas and co-workers have synthesized new generations of DHP derivatives in which the phenyl substituent at the C-4 position of the DHP ring has been replaced by other aromatic substituents such as imidazolyl and pyridine. [8][9][10][11][12] Recently, some new derivatives of DHP containing a 1-methyl-5-nitro-imidazol-2-yl substituent at the C-4 position and different ester substituents on the C-3 and C-5 positions of the DHP ring have been synthesized. [12][13][14][15][16] The calcium channel antagonist activity of the compounds in Guinea-pig Ileal was determined, and it was found that the activity of some derivatives was higher than that of nifedipine.…”
Section: Introductionmentioning
confidence: 99%
“…Some derivatives such as nifedipine, nicardipine, amlodipine, and nitrendipine are now commercially available in drug stores. Very recently, Knuas and co-workers have synthesized new generations of DHP derivatives in which the phenyl substituent at the C-4 position of the DHP ring has been replaced by other aromatic substituents such as imidazolyl and pyridine. Recently, some new derivatives of DHP containing a 1-methyl-5-nitro-imidazol-2-yl substituent at the C-4 position and different ester substituents on the C-3 and C-5 positions of the DHP ring have been synthesized. The calcium channel antagonist activity of the compounds in Guinea-pig Ileal was determined, and it was found that the activity of some derivatives was higher than that of nifedipine. Earlier, we carried out some quantitative structure−activity relationship analysis on these compounds and found that lipophilicity and steric and electronic properties are the major factors controlling the binding of these molecules to their receptor.…”
Section: Introductionmentioning
confidence: 99%